2019
DOI: 10.3324/haematol.2019.221655
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin generation in cardiovascular disease and mortality - results from the Gutenberg Health Study

Abstract: Thrombin generation may be a potential tool to improve risk stratification for cardiovascular diseases. This study aims to explore the relation between thrombin generation and cardiovascular risk factors, cardiovascular diseases, and total mortality. For this study, N=5000 subjects from the population-based Gutenberg Health Study were analysed in a highly standardized setting. Thrombin generation was assessed by the Calibrated Automated Thrombogram method at 1 and 5 pM tissue factors trigger in platelet poor p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 31 publications
0
16
1
Order By: Relevance
“…In this issue of the Journal van Paridon et al add more evidence on the mechanisms of hypercoagulability and clinically relevant outcomes. 1 They evaluated TG in a large population of subjects (n=5,000) enrolled in a prospective study with a relatively long follow-up (up to 9.65 years). The authors found that some TG parameters were independently associated with overall mortality.…”
Section: New Observations On Thrombin Generationmentioning
confidence: 99%
See 3 more Smart Citations
“…In this issue of the Journal van Paridon et al add more evidence on the mechanisms of hypercoagulability and clinically relevant outcomes. 1 They evaluated TG in a large population of subjects (n=5,000) enrolled in a prospective study with a relatively long follow-up (up to 9.65 years). The authors found that some TG parameters were independently associated with overall mortality.…”
Section: New Observations On Thrombin Generationmentioning
confidence: 99%
“…The study by van Paridon et al is the first to investigate the association of hypercoagulability (as measured by TG) and the risk of mortality in a large population. 1 However, some issues emerge from the study that warrant consideration. While it is plausible that high ETP is directly associated with overall mortality, it is less plausible that the prolonged (not shortened) lagtime is associated with mortality.…”
Section: New Observations On Thrombin Generationmentioning
confidence: 99%
See 2 more Smart Citations
“…[25][26][27] Moreover our findings are further supported by the results of the population based Gutenberg Health Study which included 5000 subjects and showed that in patients with cardiovascular disease or cardiovascular risk factors the prolongation of the lag-time of thrombin generation is associated with mortality. 28 Based on the analysis of the previously published studies a methodological approach is required for the interpretation of this finding. Thrombogram-Thrombinoscope ® assay is performed with exogenously added PPP-reagent ® which contains optimal concentrations of TF and procoagulant phospholipids (5pM and 4 mM respectively).…”
Section: Discussionmentioning
confidence: 99%